Field evaluation of the establishment potential of wmelpop Wolbachia in Australia and Vietnam for dengue control. Issue 1 (December 2015) - Nguyen, Tran; Nguyen, H.; Nguyen, Thu; Vu, Sinh; Tran, Nhu; Le, T.; Vien, Quang; Bui, T.; Le, Huu; Kutcher, Simon; Hurst, Tim; Duong, T.; et al.
Abstract Background IntroducedWolbachia bacteria can influence the susceptibility ofAedes aegypti mosquitoes to arboviral infections as well as having detrimental effects on host fitness. Previous field trials demonstrated that thew Mel strain ofWolbachia effectively and durably invadesAe. aegypti populations. Here we report on trials of a second strain, w MelPop-PGYPWolbachia, in field sites in northern Australia (Machans Beach and Babinda) and central Vietnam (Tri Nguyen, Hon Mieu Island), each with contrasting naturalAe. aegypti densities. Methods Mosquitoes were released at the adult or pupal stages for different lengths of time at the sites depending on changes inWolbachia frequency as assessed through PCR assays of material collected through Biogents-Sentinel (BG-S) traps and ovitraps. Adult numbers were also monitored through BG-S traps. Changes inWolbachia frequency were compared across hamlets or house blocks. Results Releases of adultw MelPop-Ae. aegypti resulted in the transient invasion ofw MelPop in all three field sites. Invasion at the Australian sites was heterogeneous, reflecting a slower rate of invasion in locations where background mosquito numbers were high. In contrast, invasion across Tri Nguyen was relatively uniform. After cessation of releases, the frequency ofw MelPop declined in all sites, most rapidly in Babinda and Tri Nguyen. Within Machans Beach the rate of decrease varied among areas, andw MelPop was detected for several months in an area with a relatively low mosquito density. Conclusions These findings highlight challenges associated with releasingWolbachia -Ae. aegypti combinations with low fitness, albeit strong virus interference properties, as a means of sustainable control of dengue virus transmission.